2018
DOI: 10.1111/pbi.13020
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequencing reveals rare off‐target mutations and considerable inherent genetic or/and somaclonal variations in CRISPR/Cas9‐edited cotton plants

Abstract: Summary The CRISPR /Cas9 system has been extensively applied for crop improvement. However, our understanding of Cas9 specificity is very limited in Cas9‐edited plants. To identify on‐ and off‐target mutation in an edited crop, we described whole genome sequencing ( WGS ) of 14 Cas9‐edited cotton plants targeted to three genes, and three negative (Ne) control and three wild‐type ( WT ) plants. In total, 4188–6404 unique single‐nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
129
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(144 citation statements)
references
References 56 publications
8
129
0
1
Order By: Relevance
“…However, it is possible that unintended mutations occur in some somatic cells, rare mutations that can be detected only by using more sensitive methods such as deep sequencing of relevant PCR amplicons. It is also possible that genetic variations from parental plants can alter PAMs and increase the potential off-target effect in more complex and larger polyploid genomes like cotton (Li et al, 2018). Nevertheless, the results indicate that, with careful design of guide RNA and better knowledge of the genome, the CRISPR/ Cas9 system can specifically target the pre-selected sites for mutations.…”
Section: No Off-target Mutation Detected Via Sanger Sequencing Of Pcrmentioning
confidence: 99%
“…However, it is possible that unintended mutations occur in some somatic cells, rare mutations that can be detected only by using more sensitive methods such as deep sequencing of relevant PCR amplicons. It is also possible that genetic variations from parental plants can alter PAMs and increase the potential off-target effect in more complex and larger polyploid genomes like cotton (Li et al, 2018). Nevertheless, the results indicate that, with careful design of guide RNA and better knowledge of the genome, the CRISPR/ Cas9 system can specifically target the pre-selected sites for mutations.…”
Section: No Off-target Mutation Detected Via Sanger Sequencing Of Pcrmentioning
confidence: 99%
“…With the development of modern technologies, plant breeders have the opportunity to overcome this bottleneck. Studies have demonstrated that targeted mutagenesis and precise base editing can be accurately applied for the G. hirsutum genome using genome editing systems [68][69][70][71][72][73][74][75][76][77]. Genome resequencing has identified many domestication genes associated with fiber quality and yield traits.…”
Section: Box 2 a Model For Genetic Breakdown Of Interspecific Hybridmentioning
confidence: 99%
“…Off-target effects of CRISPR-Cas systems are potential concerns in many of their applications. Whole-genome sequencing (WGS) conducted in Arabidopsis, tomato and cotton showed that off-target activity induced by SpCas9 has rarely occurred (Feng et al 2014;Nekrasov et al 2017;Li et al 2018c;Tang et al 2018). High targeting specificity was also recently reported for Cas12a in rice and cotton Li et al 2019a).…”
Section: Off-target Effects Of Crispr-cas Systemsmentioning
confidence: 94%